A First Course in Business Mathematics and Statistics / Foundation, Instruction, Right, Start, Textbooks - Rowe R.N (Dp Publications Ltd, 1991)
The aim of this book is to provide a course text for the first year of the many courses that introduce basic quantitative methods to students who do not need to be, and very often aren't, particularly mathematically minded. Preface, Introduction, Sequences and Series, Financial Mathematics, Matrices, Matrix Applications, Simultaneous Linear Equations: Solution and Formulation, Statistics, Statistical Diagrams, Frequency Distributions, Measures of Central Tendency, Measures of Variation, Probability, Probability Distributions, Binomial Distribution, Normal Distribution, Correlation and Regression.